TECHNICAL GUIDANCE FOR IMPROVING THE USE AND UTILIZATION OF DRONE DATA IN WEST ACEH LAND AGENCY - Alvisyahri, Alvisyahri; Idris, Fadli; Fachruddin, Fachruddin; Rahman, Aulia; Malia, Rezqi; Dinda, Raina Parmitalia (Universitas Muhammadiyah Aceh, 2023)
Drones are advanced technology that can help humans in transportation because they can see almost everything and save human energy. In fact, in some cases, they may not disrupt traffic like regular vehicles. The Technical Guidance Activity to Increase Capacity in the Use and Utilization of Drone Data (UHV/Unmanned Aerial Vehicle) is intended to provide West Aceh District Land Service officials with insight and knowledge about the use and utilization of drone data. The purpose of this service is to provide an introduction and insight to West Aceh District Land Service officials regarding the use and utilization of drone data (UHV/Unmanned Aerial Vehicle) as well as providing direction and knowledge about the steps for implementing the use and utilization of drone data. The Technical Guidance Activity for Increasing the Capacity of Use and Utilization of Drone Data (UHV/Unmanned Aerial Vehicle) for West Aceh Regency Land Service officials is an activity held by the USK Forestry Research Center in collaboration with Teuku Umar University on Wednesday 15 February 2023 from at 08.30 until finished. The theme of the material provided is Mapping Using Drones and its application in making contour maps with the help of GIS applications. The method used is a presentation. With this technical guidance regarding the Use and Utilization of Drone Data (UHV/Unmanned Aerial Vehicle), participants understand the ease of processing map data, especially those related to land mapping. Keyword : Drone, UHV/Unmanned Aerial Vehicle, Mapping